Effects of ticlopidine on metoprolol pharmacokinetics in major CYP2D6 genotypes within Malaysian subjects with cardiovascular diseases - Wan Mohd Azizi bin Wan Sulaiman (Kulliyyah of Medicine, International Islamic University Malaysia, 2010)
Ticlopidine is used as an anti-platelet drug in patients with ischaemic heart disease. An in vitro study suggested that ticlopidine inhibited CYP2D6 and the widely used antianginal metoprolol is metabolized by this polymorphic enzyme. The objective of this study to investigate the effect of ticlopidine treatment in patients maintained on chronic metoprolol therapy. The study was approved by the Ethics Committee of International Islamic University Malaysia (IIUM) and strictly adhered to Malaysian Good Clinical Practice (GCP) guidelines. This was an open labelled Case Controlled Study where all the patients were screened for the inclusion and exclusion criteria. CYP2D6 genotyping were performed for *3,*4,*5,*6,*9,*10, *14, *17 and duplication. Two weeks after the screening visit, blood for metoprolol was taken at timed intervals together with serial measurement of blood pressures and heart rates. Subsequently the patients were given a standard dose of ticlopidine 250 mg twice daily for a period of one month. At the end of study period, blood for metoprolol was repeated together with serial measurement of blood pressures and heart rates. Eighty seven patients completed the study. The frequency of predicted Poor Metabolizer (PM) was low at 2.6%, where both patients had homozygous *4/*4 and the majority (47.8%) carried the allele *10, predicted Intermediate Metabolizer (IM). After ticlopidine treatment, there were increasing trend within the metoprolol pharmacokinetic parameters among the different predicted phenotypes and different allele variations. Plasma Metabolic Ratio was significantly different (p< 0.05) between phenotypes and allele variations. The two Poor Metabolizers (PM) patients presented with bradycardia even at doses of 25 mg and 50 mg twice daily. There were wide variations among the CYP2D6*10 allele group for metoprolol pharmacokinetic parameters, suggesting the presence of a subgroup population that may overlap features with the Poor Metabolizer group. However, there were no significant change for both pre and post ticlopidine for blood pressure control and heart rate. After ticlopidine, there was a neutrophil count reduction in 32 patients and 6 patients had neutropenia with neutrophil count less than 2.5 x 10³ / μl. Concurrent use of ticlopidine with metoprolol may subject patients who are poor CYP2D6 metabolisers to have exaggerated response to beta blockade and blood dyscrasias may occur frequently.